Preparation of Kerosene Based Carbon Nanomaterials by Nebulized Spray Pyrolysis - Arie, Arenst Andreas; Widjaja, Ongky; Susanti, Ratna Frida; Devianto, Hary; Halim, Martin; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2017)
In this study, carbon nanomaterials were prepared using a nebulized spray pyrolysis process. A mixed solution of from kerosene oil and dissolved ferrocene catalyst was nebulized into droplets which were then carried by N-2 gas flow through a furnace tube. Upon heating, the oil was decomposed onto the surface of activated carbons. By varying the catalyst concentration dissolved in the oil (0.015, 0.02 and 0.025 g/ml) and operating temperature (650, 700 and 750 degrees C), the structure or morphology of the as-prepared carbon nanomaterials can be adjusted. The structure and morphology of the carbon samples were observed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Their graphite crystallinity was analyzed using Raman spectroscopy. The experimental results showed that carbon nanospheres (CNSs) formed at a lower catalyst concentration (0.015 and 0.02 g/ml), whereas carbon nanotubes (CNTs) were obtained at a higher concentration (0.025 g/ml) for deposition conducted at 700 degrees C. Similarly, agglomerated CNSs were also observed for deposition done at 650 and 750 degrees C and catalyst concentration of 0.02 g/ml.